Effect of high-intensity interval training on expression of pro and anti-apoptotic genes in myocard tissue of aged male C57BL/6 mice - Rahman Soori; Maryam Zare Shahneh; Sirus Choubineh; Azam Ramezankhani (Shahid Beheshti University, 2019)
Purpose: Bax and BCL-2 genes are important genes that involve in the intrinsic pathway of apoptosis. Although the effects of interval and intensive exercises on the mechanisms involved in the gaining processes are less considered. So, the aim of the present study was to investigate the effect of high-intensity interval training on the expression of pro and anti-apoptotic genes (Bax and BCL-2) in myocard in aged male mice.Methods: This experimental study was performed on twenty 24- months old C57BL/6 mice. Animals were randomly assigned to the control (n=10) and experimental groups (n=10). The experimental group performed high interval intensity training for four weeks (five sessions per week). At first, the interval training started at the intensity equal to 85 percent of maximum speed and in the continuation of interval training, 5 percent was added weekly and the last two weeks ended with 95 percent rate. Forty-eight hours after the last training session, myocardial muscle was removed. Bax and BCL-2 genes expression were investigated by SYBR-Green Real-time PCR analysis.Results: The results of Real Time-PCR showed that the average relative expression of pro-apoptotic Bax gene was significantly lower in the experimental group than in the control group (0.618±0.022 vs. 1 unit; P<0.05). Also, the average relative expression of Anti-apoptotic Bcl2 gene expression was higher in the experimental group than in the control group (1.824±0.084 vs. 1 unit; P< 0.05).Conclusion: The results showed that high-intensity interval training by modifying the expression of pro and anti-apoptotic genes (Bax and BCL-2) may be effective in reducing apoptosis in cardiac tissue of aged mice.